Sistem Water Level Control Untuk Budidaya Ikan Gurame Menggunakan Logika Fuzzy Berbasis Mikrokontroler - Sriani Sriani; Franindya Purwaningtyas (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2018)
Control system automation technology and microcontroller is one way that is used to detect waterconditions and water levels as well as a system to automatically control a water pump. The process ofautomation in regulating water levels is very important in order to save water requirements in fishponds. In this study, automation technology was made using microcontroller-based fuzzy logic, for asystem of detecting water conditions and water levels and a system for controlling water pumps, whichcan be adjusted automatically according to the upper limit (maximal) and lower limit (minimum) andcan replace pool water automatically when the pool water is cloudy.Keywords: Water, fuzzy logic, microcontroller